Pathology of practolol-induced ocular toxicity. - Rahi, A H (1976)
The ocular side-effects of prolonged practolol administration concern the cornea and conjunctiva and are related to deficient tear secretion and the formation of an autoantibody which has an affinity for the intercellular zones of squanmous epithelium. Histopathological study of six cases, including a review of the necropsy findings in two, showed destruction of lacrimal gland tissue, epidermalization of the conjunctival epithelium, with epitheliolysis and stromal ulceration of the cornea leading to perforation in two patients. Immunoperoxidase studies showed fixation of specific antibody in the corneal and conjunctival epithelium but, in the one case in which the tissue could be adequately studied, complement fixation could not be demonstrated. Possibly, therefore, the immune response in patients with practolol-induced ocular damage is secondary to the epithelial disturbance rather than its cause.